Perbaikan Musala dan Mengajar Ngaji untuk Meningkatkan Kenyamanan Ibadah dan Mengaji - Fuad Indra Kusuma; Moh. Edo Abdulloh; Fani Maulana; Fuad Indra Kusuma; Moh. Edo Abdulloh (Universitas Negeri Malang, 2021)
Abstract: It is common that a mosque or prayer room is very important for Muslims, where the mosque or prayer room is used as a place of worship for Muslims such as praying, reading the Koran and others. The construction of a mosque or prayer room is a gift from Allah, because the mosque is the house of Allah on earth. The mosque is the most noble, most sacred house that Allah has placed on earth. Therefore, we as Muslims should clean, care for, and renovate if there is something that needs to be repaired. The 2021 UM KKN group in Donomulyo village took the initiative to renovate the prayer room in Mulyosari hamlet, Donomulyo village, Donomulyo District, Malang Regency. With this renovation activity, it is hoped that it will become a medium for KKN friends in Donomulyo village and the surrounding community as well as to gather or take care of the prayer room that is there, because there are several things that need to be repaired in the prayer room, moreover, the location targeted by the community service friends it's far from the crowds or the city. From there, the Donomulyo Village Community Service Group in 2021 took the initiative to renovate the prayer room and also help teach the cabai rawit brothers who were there. Abstrak: Sudah menjadi hal umum bahwa sebuah masjid atau musala menjadi hal yang sangat penting bagi umat islam, yang mana masjid atau musala digunakan sebagai tempat ibadah umat islam seperti melaksanakan sholat, mengaji dan lain-lain. Dibangunnya sebuah masjid atau musala itu merupakan salah satu anugerah dari allah, karena masjid merupakan rumah allah di muka bumi. Masjid adalah rumah yang paling mulia, yang paling suci yang allah letakkan di muka bumi. Oleh sebab itu seyogyanya kita sebagai umat islam untuk membersihkan, merawat, serta merenovasi apabila ada yang perlu diperbaiki. Kelompok KKN UM 2021 di desa Donomulyo berinisiatif renovasi musala yang ada di dusun Mulyosari, desa Donomulyo, Kecamatan Donomulyo, Kabupaten Malang. Dengan adanya kegiatan renovasi ini diharapkan bisa menjadi media bagi temen-temen KKN desa Donomulyo dengan masyarakat sekitar sekaligus untuk merawat atau merawat musala yang ada disana, karena ada beberapa hal yang perlu diperbaiki pada musala tersebut, terlebih, lokasi yang dituju oleh temen-temen KKN ini jauh dari keramaian atau kota. Dari situlah kelompok KKN desa Donomulyo tahun 2021 berinisiatif untuk renovasi musala serta juga ikut membantu mengajar adik-adik caberawit yang ada disana.